Endoscopic Management of Biliary Complications following Liver Transplantation after Donation from Cardiac Death Donors - Kris P Croome; Vivian McAlister; Paul Adams; Paul Marotta; William Wall; Roberto Hernandez-Alejandro (Canadian Journal of Gastroenterology)
BACKGROUND Previous studies have shown a higher incidence of biliary complications following donation after cardiac death (DCD) liver transplantation compared with donation after brain death (DBD) liver transplantation. The endoscopic management of ischemic type biliary strictures in patients who have undergone DCD liver transplants needs to be characterized further.